Magnetoresistance of Ni/WSe2/Ni junctions: robustness against the thickness of WSe2. (17th September 2022) - Yan, Kun; Hu, Yizhi; Suo, Yan; Qin, Yuxia; Chen, Xiaobin
Abstract: Magnetoresistive materials are vital for the development of storage devices. Using the first-principles transport simulations with nonequilibrium Green's function calculation, we investigate the magnetoresistive properties of Ni/WSe2 /Ni junctions with m -layers of WSe2 ( m = 1, 2, ⋯, 6). For m ≤ 2, the junctions are metallic inspite of the semiconducting nature of few-layer WSe2 . However, the junctions exhibit transport gaps for m > 2. Interestingly, magnetoresistance of the junctions stays around 6% when there are more than one layer of WSe2 in the center, which is closely related to the robust spacial variation of interfacial properties and can be attributed to no spin flipping in tunneling regions. Our results suggest that Ni/WSe2 /Ni junctions have a robust magnetoresistance which is insensitive to the thickness of WSe2 .